A road map for implementing lean and agile techniques in SMEs product development teams. (2016) - Leite, Marco; Baptista, A.J.; Ribeiro, A.M.R.
The aim of this research paper is to formulate a road map for implementation of lean techniques within SMEs product development (PD) teams, identifying barriers to change and explaining possible drivers for successful implementation. The research methodology necessary to develop the road map - the IPID cycle - is a combination of different approaches. It combines a literature review, an initial quantitative study with questionnaires, informal interviews and direct observation of companies' practices of five different manufacturing companies organised in a consortium. Like any other case study methodology, it suffers from generalisation issues, but we expect that the proposed road map is applicable whenever managers need to introduce changes inside their PD teams. Also, we found that a consortium arrangement can be highly positive to the implementation of the proposed road map. Finally, we found that the application of the road map to SMEs PD teams is somewhat different from big companies' implementations and discuss the observed particularities of these findings.